Quantitative systems pharmacology model of erythropoiesis to simulate therapies targeting anemia due to chronic kidney disease - Roy, Mrittika; Saroha, Shaifali; Sarma, Uddipan; Sarathy, Harini; Kumar, Rukmini (Frontiers in Pharmacology, 2023)
Anemia induced by chronic kidney disease (CKD) has multiple underlying mechanistic causes and generally worsens as CKD progresses. Erythropoietin is a key endogenous protein which increases the number of erythrocyte progenitors that mature into red blood cells that carry hemoglobin (Hb). Recombinant Erythropoietin (rHuEPO) in its native and re-engineered forms is used as a therapeutic to alleviate CKD induced anemia by stimulating erythropoiesis. However, due to safety risks associated with these Erythropoiesis Stimulating Agents (ESAs), a new class of drugs Prolyl Hydroxylase Inhibitors (PHIs) are being developed. Instead of administering exogenous EPO, PHIs facilitate accumulation of HIF-α which results in increased production of endogenous EPO. Clinical trials for ESAs and PHIs generally involve balancing decisions relating to safety and efficacy by carefully evaluating criteria for patient selection and adaptive trial design. To enable such decisions, we have developed a Quantitative Systems Pharmacology (QSP) model of erythropoiesis which captures key aspects of physiology and its disruption in CKD. Further, CKD Virtual Populations of varying severity were developed, calibrated, and validated against public data. Such a model can be used to simulate alternative trial protocols while designing Phase 3 clinical trials, as well as an asset for reverse translation in understanding emerging clinical data.However, the model calibration did not include Reticulocytes, consequently, the comparison of data and simulations for Reticulocytes is omitted.Additional details about model design, equations and methods are provided in the Supplementary Appendix file. The model file and the scripts required to generate the results have been uploaded to GitHub.